2021
DOI: 10.5312/wjo.v12.i6.376
|View full text |Cite
|
Sign up to set email alerts
|

Off-the-shelf 3D printed titanium cups in primary total hip arthroplasty

Abstract: Three-dimensional (3D)-printed titanium cups used in primary total hip arthroplasty (THA) were developed to combine the benefits of a low elastic modulus with a highly porous surface. The aim was to improve local vascularization and bony ingrowth, and at the same time to reduce periprosthetic stress shielding. Additive manufacturing, starting with a titanium alloy powder, allows serial production of devices with large interconnected pores (trabecular titanium), overcoming the drawbacks of tantalum and conventi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

0
2
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 7 publications
(2 citation statements)
references
References 37 publications
0
2
0
Order By: Relevance
“…3D-printed titanium cups offer distinct advantages in orthopedic applications. These cups feature a porous and rough surface, theoretically promoting local vascularization and osseointegration while mitigating stress shielding due to their low elastic modulus [ 48 ]. Unlike other highly porous titanium cups produced through conventional methods, 3D-printed cups exhibit larger pore sizes and higher porosity, thereby replicating a trabecular bone-like elastic modulus.…”
Section: Reviewmentioning
confidence: 99%
See 1 more Smart Citation
“…3D-printed titanium cups offer distinct advantages in orthopedic applications. These cups feature a porous and rough surface, theoretically promoting local vascularization and osseointegration while mitigating stress shielding due to their low elastic modulus [ 48 ]. Unlike other highly porous titanium cups produced through conventional methods, 3D-printed cups exhibit larger pore sizes and higher porosity, thereby replicating a trabecular bone-like elastic modulus.…”
Section: Reviewmentioning
confidence: 99%
“…The ability of additive manufacturing to integrate surface porosity within a monoblock implant is key to improving osseointegration and potentially reducing stress shielding by mimicking the stiffness of the periprosthetic bone [ 50 ]. It was shown that 3D-printed cups maintain acceptable micromotion, even surpassing conventional cups with lower wall thickness [ 48 ]. The combination of wall thickness and a highly porous surface contributes to the stability of 3D cups.…”
Section: Reviewmentioning
confidence: 99%